Peroxidation processes in ocular surface tissues in experimental hypothyroidism - Drozhzhyna G.I; Pavlovskii M.I; Pavlovskaia G.Ia (Ukrainian Society of Ophthalmologists, 2019)
Background. It is known that a decreased level of thyroid hormones (TH) in the body causes hypothyroidism and is accompanied by metabolic, functional and structural changes in different organs and tissues, including an eye and tear glands, in particular. However, these changes in the conjunctiva, cornea, and tear fluid have not been studied. It has been shown in experiment that the decreased TH level can lead to the development of dry eye syndrome. The thyroid hormones induce the changes in the tear fluid and have an effect on the epithelium of ocular surface tissues although the mechanisms of this effect are understudied. The changes in the ocular surface tissues in the presence of hypothyroidism are also unclear. Purpose. To study experimentally the state of lipid peroxidation processes in the cornea, conjunctiva, and tear fluid on a model of hypothyroidism in rats. Material and Methods. Male white Wistar rats were used in the experiment. Forty-two animals were randomly divided into 3 groups: group 1, fourteen rats serving as control; group 2, fourteen rats with early hypothyroidism; group 3, fourteen rats with pronounced hypothyroidism. Hypothyroidism was induced by antithyroid tiamazole which the rats in the study groups received with drinking water (500 mg/l) for four and ten weeks to simulate early and pronounced hypothyroidism, respectively. We evaluated spectrophotometrically the content of malondialdehyde and diene conjugates in the tissues studied [5]. Results. In experimental hypothyroidism, the lipid peroxidation (LPO) processes are activated in the ocular tissues, which is evidenced by the increased content of malondialdehyde and diene conjugates in the conjunctiva by 85.6% and 55.6%, respectively, and in the cornea by 51.3% and 25.4%, respectively, especially in pronounced hypothyroidism. The highest rates of malondialdehyde were noted in pronounced hypothyroidism. The sharpest increase of malondialdehyde was in the tear fluid: by 70.2% and 101.3% in early and pronounced hypothyroidism, respectively. Conclusions. The increased content of malondialdehyde in the cornea, conjunctiva, and, especially, tear fluid, gives evidence of the activated LPO processes and depends on the stage of experimental hypothyroidism. The data obtained make it possible to consider a level of malondialdehyde in the tear as a biochemical indicator of damage to ocular surface tissues in hypothyroidism.